2004
DOI: 10.1152/ajprenal.00401.2003
|View full text |Cite
|
Sign up to set email alerts
|

Effects of calcium channel blockers on “dynamic” and “steady-state step” renal autoregulation

Abstract: Effects of calcium channel blockers on "dynamic" and "steady-state step" renal autoregulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
75
0
5

Year Published

2004
2004
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 47 publications
(84 citation statements)
references
References 43 publications
4
75
0
5
Order By: Relevance
“…The myogenic response is much faster, with a natural frequency of 0.1-0.2 Hz in the anaesthetized rats and 0.2-0.3 Hz in conscious animals (2,32,36,38,56,76,122,165,166). Essentially similar data regarding the kinetics of these mechanisms have been obtained through analyses of RBF responses to step changes in BP (84,85,102,175).…”
Section: Bp Variability and The Requirements For Protection Vs Regulmentioning
confidence: 74%
See 1 more Smart Citation
“…The myogenic response is much faster, with a natural frequency of 0.1-0.2 Hz in the anaesthetized rats and 0.2-0.3 Hz in conscious animals (2,32,36,38,56,76,122,165,166). Essentially similar data regarding the kinetics of these mechanisms have been obtained through analyses of RBF responses to step changes in BP (84,85,102,175).…”
Section: Bp Variability and The Requirements For Protection Vs Regulmentioning
confidence: 74%
“…Dynamic autoregulatory studies, employing transfer function and frequency domain analyses, have revealed the natural frequency of the TGF mechanism in the rat to be in the range of 0.05 Hz (2,32,36,38,56,76,122,165,166). The myogenic response is much faster, with a natural frequency of 0.1-0.2 Hz in the anaesthetized rats and 0.2-0.3 Hz in conscious animals (2,32,36,38,56,76,122,165,166).…”
Section: Bp Variability and The Requirements For Protection Vs Regulmentioning
confidence: 99%
“…[74][75][76][77] Recently T-type channels have also been implicated in the myogenic response of several vascular beds although some studies show that the influence of T-type channels on the myogenic response is more pronounced in the lower pressure range where the VSMC are less depolarized. 46,78,79 In the renal vascular bed inhibition of T-type channels reduce autoregulation, 80,81 but whether this effect is caused by an attenuation of the myogenic response alone or also affects the TGF is unknown. Both mechanisms affect resistance in the afferent arteriole.…”
Section: Myogenic Responsementioning
confidence: 99%
“…90,91 Some studies have also shown that inhibition of renal T-type channels significantly affects autoregulation. 80,81 However, due to the lack of specific inhibitors of T-type channels results have been difficult to interpret.…”
Section: Renal Autoregulationmentioning
confidence: 99%
See 1 more Smart Citation